Relationship of the employment policy with rural development in the European Union - Béresné Mártha, Bernadett (Acta Agraria Debreceniensis, 2009)
Employment policy has won primary attention both at national and EU levels for the past decade. Managing its problems has become one of the major social economic and political challenges. One of the problems is the aging of the continent’s population, which is in close relation with the slow increasing or decreasing economic trends. Comparing the EU’s unemployment, employment and labour productivity rates to those of ten years earlier a positive tendency can be traced. On of the other hand compared with the USA, Japan or the average of OECD countries the Community has still not been able to reduce its several decades lasting leeway. Difficulties of labour management are much more striking in rural territories than in urban districts. Not even the second pillar of the Common Agricultural Policy: the rural development has been successful in managing the employment of the labour superseded from the primer sector so far, which is significantly reflected in the unfavourable indicators of labour management and unemployment.